Analysis of the Level of Road Damage and Maintenance Using the International Rougness Index (IRI) Method (A Case Study in Malang City) - Imam Gusti Argawana; Henri Siswanto; Boedi Rahardjo (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
Poor road conditions can put drivers at risk, lead to accidents, and create inconvenience and inefficiency on the road. Road maintenance is crucial to keep roads functioning optimally. This research aims to analyze the level of road damage using the IRI (International Roughness Index) and determine the type of maintenance required. The research was conducted on four main streets in Malang City. IRI data was obtained from field surveys using the Roadroid application. The data that has been obtained is processed and analyzed to determine the level of damage and the type of maintenance required. The results of this research are: Tidar Street is 21.05% in good condition, and the remaining 78.95% is in fair condition. Candi V Street is 27.27% in good condition, and 72.73% is in fair condition. Karang Ampel Street is 69.23% in good condition, 23.08% in fair condition, and 7.69% in lightly damaged condition. Bendungan Wonogiri Street is 50% in good condition and 50% in fair condition. The type of maintenance for Tidar Street is determined using the average IRI value approach. With a value of 4.87, Tidar Street requires periodic maintenance. Meanwhile, Candi V Street, Karang Ampel Street, and Bendungan Wonogiri Street are maintained using a segment group system, with each road section requiring two types of maintenance, namely routine maintenance and periodic maintenance.